Spanish nobility in the Second Republic (1931-‍1936): An elitist radicalization - Hernández Barral, José Miguel (Historia y Política, 2019)
During II Spanish Republic, political mobilization was a key matter for the nobility. Passivity, plot involvement or party militancy: all these attitudes were displayed by the noblemen and women in a just newborn regime. The study of this social group questions traditional interpretations on right-wing attitudes in the Second Republic, what have substantial consequences until the end of the regime, even for the Spanish Civil War and the Francoism. The article tackles some key events from the point of view of the nobility: Republic proclamation, the 10th May events and the Sanjurjo coup. Moreover, it is offered a new approach to the Grandees of Spain expropriation and its connection with their political mobilization. The aristocracy decisions, strategies and paradoxes allow us to understand more deeply the right-wing evolution in the Republic, adding the elitist dimension of the group to the complex processes of deliberalization, fascistization and capture by the radical nationalism.